Q. 95.0( 2 Votes )

Let f : Z

Answer :

To find: g : Z Z : g o f = IZ


Formula used: (i) f o g = f(g(x))


(ii) g o f = g(f(x))


Given: (i) g : Z Z : g o f = IZ


Solution: We have,


f(x) = 2x


Let f(x) = y


y = 2x





Where g: Z Z


For g o f,


g(f(x))


g(2x)



x = IZ


Clearly we can see that (g o f) = x = IZ



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar